A novel homozygous mutation (Gly1715Ser) causing hereditary factor V deficiency in a Chinese patient. Issue 1 (January 2020) - Liu, Siqi; Luo, Shasha; Yang, Lihong; Jin, Yanhui; Xie, Haixiao; Xie, Yaosheng; Li, Xiaolong; Wang, Mingshan
Abstract : N/A: To explore the phenotype and genotype of a Chinese family with hereditary factor V deficiency. Routine blood coagulation indexes were detected by one-stage clotting method, whereas factor V antigen was detected by ELISA. All exons and intron–exon boundaries of F5 gene were amplified by PCR and sequenced directly. The suspected mutation was confirmed by reverse sequencing. Bioinformatics softwares were used to analyze the possible impact of this mutation. Phenotypic analysis showed that the proband had significantly prolonged prothrombin time and activated partial thromboplastin time, and his factor V clotting activity was decreased to 3%. Genetic analysis revealed a homozygous missense mutation c.5227G>A (p.Gly1715Ser) in exon 16 of F5 gene. Bioinformatics and structural analysis demonstrated this mutation was deleterious and could affect the integrity of local intermolecular structures. The missense mutation (Gly1715Ser) was responsible for the decrease of factor V clotting activity and factor V antigen in this family, and caused type I hereditary factor V deficiency.